Odpowiedzi

2010-02-19T10:13:01+01:00
A) x + (3x-y+5) = x+3x-y+5 = 4x - y + 5


b) -x+(2x-3y-1) = -x+2x-3y-1 = x-3y-1


c)3(x+2y-5) = 3x+6y-15


d) 5 (a-2b-1) - 3 (a-5b) = 5a-10b-5
2010-02-19T10:13:38+01:00
Nie wiem czy podalaś wszystkie dane wydaje mi się że nie ale:
a/ 4x+5-y
b/ x-3y-1
c/ 3x+6y-15
d/ 5a-10b-5 - 3a +5b= 2a - 5b - 5
Najlepsza Odpowiedź!
2010-02-19T10:14:01+01:00
A) x + (3x-y+5) =x+3x-y+5=4x-y-5
b) -x+(2x-3y-1)=-x+2x-3y-1=x-3y-1
c)3(x+2y-5)=3x+6y-15
d) 5 (a-2b-1) - 3 (a-5b)=5a-10b-5-3a+15b=2a+5b-5

mam nadzieje ze dobrze ;)
pozdrawiam :*